Synergistic effect of sandwich polyoxometalates and copper–imidazole complexes for enhancing the peroxidase-like activity1. Issue 96 (17th October 2015) - Chai, Dong-Feng; Ma, Zhuo; Yan, Hong; Qiu, YunFeng; Liu, Hong; Guo, Hua-Dong; Gao, Guang-Gang
<x xml:space="preserve">Abstract</x> Two inorganic–organic hybrids based on copper(ii)–imidazole complex modified sandwich-type tungstobismuthate or tungstoantimonite, have been synthesized, demonstrating higher peroxidase-like activity using TMB as a peroxidase substrate.